6m-1=2(m-5)-3

Simple and best practice solution for 6m-1=2(m-5)-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6m-1=2(m-5)-3 equation:



6m-1=2(m-5)-3
We move all terms to the left:
6m-1-(2(m-5)-3)=0
We calculate terms in parentheses: -(2(m-5)-3), so:
2(m-5)-3
We multiply parentheses
2m-10-3
We add all the numbers together, and all the variables
2m-13
Back to the equation:
-(2m-13)
We get rid of parentheses
6m-2m+13-1=0
We add all the numbers together, and all the variables
4m+12=0
We move all terms containing m to the left, all other terms to the right
4m=-12
m=-12/4
m=-3

See similar equations:

| 285/4c=0 | | T(n)=0.75n | | 6x+7=5-2x | | 15x+36=0 | | 4x+4=2×-24 | | 18-4h=6-16h | | -12=-3(s-11) | | -6h+4.5=13.5 | | 3y=12-4,3y=8,y=8/3 | | -2p/6-19=-9 | | 12x=203/5 | | 14+5p=34 | | -2q+18=-18+4q | | 1/8y=2-3 | | 12+b̸=42 | | -2(x=4)=16 | | 3y^2−31y+80=0 | | -21=-2y-3 | | 35+2x=63 | | 2/9y²-5y+18=0 | | .5x-12=-3 | | 4c−5=5c | | 2(x+1)+9=4x-2(-5+x) | | -54=5x-19 | | -15h=-14h-15 | | r=3(9r-3)+6 | | 2y²-45y+162=0 | | 8+32n=31n=17 | | 3c+5=2c-7 | | 3(a+2)=4a+1 | | (k-7,2k)=(-k-1,k+2) | | 3(2x+1)+4=16 |

Equations solver categories